Explosion-proof rubber jacketed aluminum alloy conductor cable for coal mine and preparation method thereof
By using rubber bodies, dioctyl terephthalate, ethylene-vinyl acetate copolymer and other materials in the cable, and adding nano zinc oxide, modified filler agent and silane coupling agent to blend the lanthanum synergistic agent, the shortcomings of existing cables in chemical corrosion resistance, impact resistance and explosion-proof performance are solved, and the coordinated improvement and performance improvement of the cable are achieved.
Patent Information
- Application Number
- CN202411919734.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing cables have shortcomings in chemical corrosion resistance, impact resistance and explosion-proof performance, making it difficult to achieve coordinated improvements, limiting the efficiency of the product.
The rubber body, dioctyl terephthalate, ethylene-vinyl acetate copolymer is used to combine nano zinc oxide and vulcanizing agent, and a modified filler and silane coupling agent are added to blend the lanthanum synergistic agent. The explosion-proof rubber sleeve aluminum alloy conductor cable for coal mines is prepared through coordinated coordination.
It significantly improves the impact resistance, explosion resistance and solvent corrosion resistance of the cable, ensuring the reliability and safety of the product in use.
Smart Images

Figure BDA0005207660620000101 
Figure BDA0005207660620000111
Abstract
Description
Technical Field
[0001] The invention relates to the field of cable technology, and in particular to an explosion-proof rubber-sheathed aluminum alloy conductor cable for coal mines and a preparation method thereof. Background Art
[0002] The existing cables have the problems of weak chemical corrosion resistance, complex process and low performance level. In order to improve their corrosion resistance, it is easy to lead to poor impact resistance and explosion resistance of the product. It is difficult to achieve coordinated improvement of the impact resistance, explosion resistance and chemical corrosion resistance of the product, which limits the use efficiency of the product. Based on this, the present invention further improves it. Summary of the invention
[0003] In view of the defects of the prior art, the purpose of the present invention is to provide an explosion-proof rubber-sheathed aluminum alloy conductor cable for coal mines and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0004] The present invention solves the technical problem by adopting the following technical solution:
[0005] The present invention provides an explosion-proof rubber sheathed aluminum alloy conductor cable for coal mines, and the explosion-proof rubber sheathed aluminum alloy conductor cable for coal mines comprises the following raw materials in parts by weight:
[0006] 20-25 parts of rubber body, 25-30 parts of dioctyl terephthalate, 10-15 parts of ethylene-vinyl acetate copolymer, 6-9 parts of nano zinc oxide, 4-7 parts of modified filler, 3-6 parts of silane coupling agent and lanthanum synergist, 2-5 parts of vulcanizer and 1-3 parts of carbon black.
[0007] Preferably, the cable comprises the following raw materials in parts by weight:
[0008] 22.5 parts of rubber body, 27.5 parts of dioctyl terephthalate, 12.5 parts of ethylene-vinyl acetate copolymer, 7.5 parts of nano zinc oxide, 5.5 parts of modified filler, 4.5 parts of silane coupling agent and lanthanum synergist, 3.5 parts of vulcanizing agent, and 2 parts of carbon black.
[0009] Preferably, the rubber body is a compound of natural rubber and styrene-butadiene rubber in a weight ratio of 3:1;
[0010] The vulcanizing agent is diisotoluene peroxide.
[0011] Preferably, the preparation method of the modified filler is:
[0012] S01: Mix the hollow glass microspheres thoroughly in a sufficient amount of 5-7% potassium permanganate solution, then wash with water and dry;
[0013] S02: 3 to 5 parts of dried hollow glass microspheres, 1 to 3 parts of yttrium nitrate solution and 2 to 4 parts of 5% by mass sodium dodecylbenzene sulfonate solution are uniformly mixed to obtain a glass microsphere liquid;
[0014] S03: adding 2 to 5 parts of sodium alginate powder and 1 to 3 parts of nano-silicon powder to 4 to 7 parts of chitosan solution and stirring thoroughly, then washing with water and drying to obtain modified sodium alginate;
[0015] S04: Add 3-5 parts of kaolin, 2-4 parts of modified sodium alginate and 1-3 parts of carboxymethyl cellulose to 4-7 parts of glass microbead liquid and stir. After stirring, filter and dry to obtain a modified filler.
[0016] Preferably, the mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the chitosan solution is 3-6%.
[0017] Preferably, the stirring speed of the stirring treatment is 550 to 750 r / min, and the stirring time is 20 to 30 min.
[0018] Preferably, the preparation method of the silane coupling agent and the lanthanum synergist is:
[0019] S01: mixing a silane coupling agent, deionized water and an ethanol solvent in a weight ratio of 2:5:1 to obtain a modified silane coupling agent;
[0020] S02: Mix lanthanum oxide with a sufficient amount of sodium silicate solution and perform ball milling at a ball milling speed of 1000-1500 r / min for 1 hour to obtain lanthanum oxide solution;
[0021] S03: Add 2 to 5 parts of lanthanum oxide liquid and 1 to 3 parts of flaky talc powder to 5 to 8 parts of sodium citrate solution, then add 2 to 4 parts of modified silane coupling agent, stir and mix thoroughly, then wash with water, filter and dry to obtain silane coupling agent and lanthanum synergist.
[0022] Preferably, the silane coupling agent is silane coupling agent KH560; the mass fraction of the sodium silicate solution is 2-5%; and the mass fraction of the sodium citrate solution is 3-6%.
[0023] The present invention also provides a method for preparing an explosion-proof rubber-sheathed aluminum alloy conductor cable for coal mines, comprising the following steps: fully mixing the raw materials according to weight parts, and then extruding and molding them at an extrusion temperature of 165° C. to obtain the cable of the present invention.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The invention adopts rubber body, dioctyl terephthalate, ethylene-vinyl acetate copolymer, nano zinc oxide and vulcanizing agent, and the modified filler, silane coupling agent and lanthanum synergist are added at the same time, and the two are coordinated and coordinated, and the obtained product has remarkable impact resistance, explosion-proof and solvent resistance and corrosion stability. The modified filler in the product adopts kaolin and other additives to optimize the explosion-proof property of the product. The explosion-proof property is an important measure to prevent explosion accidents, and the product has reliable explosion-proof property; the modified filler adopts glass microspheres, which are activated and improved by potassium permanganate solution, and then uniformly blended by yttrium nitrate solution and 5% by mass sodium dodecylbenzene sulfonate solution to optimize the dispersion of hollow glass microspheres. and activity, sodium alginate powder and nano silicon powder are added to chitosan solution and stirred sufficiently to obtain modified sodium alginate, kaolin, modified sodium alginate and carboxymethyl cellulose are added to glass microbead solution for blending and reconciliation, the interface of the system is optimized through the coordination between the raw materials, and the coordination and improvement effect between the raw materials is improved, silane coupling agent is used to blend lanthanum synergist, silane coupling agent is modified, blended and matched with lanthanum oxide in a sufficient amount of sodium silicate solution, and ball milled, and at the same time, flaky talc powder, sodium citrate solution and modified silane coupling agent are blended and coordinated, the coordination effect of silane coupling agent blending lanthanum synergist and modified filler is enhanced, so that the performance of the product is further improved. DETAILED DESCRIPTION
[0026] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] An explosion-proof rubber sheathed aluminum alloy conductor cable for coal mines, comprising the following raw materials in parts by weight:
[0028] 20-25 parts of rubber body, 25-30 parts of dioctyl terephthalate, 10-15 parts of ethylene-vinyl acetate copolymer, 6-9 parts of nano zinc oxide, 4-7 parts of modified filler, 3-6 parts of silane coupling agent and lanthanum synergist, 2-5 parts of vulcanizer and 1-3 parts of carbon black.
[0029] Preferably, the cable comprises the following raw materials in parts by weight:
[0030] 22.5 parts of rubber body, 27.5 parts of dioctyl terephthalate, 12.5 parts of ethylene-vinyl acetate copolymer, 7.5 parts of nano zinc oxide, 5.5 parts of modified filler, 4.5 parts of silane coupling agent and lanthanum synergist, 3.5 parts of vulcanizing agent, and 2 parts of carbon black.
[0031] The rubber body is a compound of natural rubber and styrene-butadiene rubber in a weight ratio of 3:1;
[0032] The vulcanizing agent is diisotoluene peroxide.
[0033] The preparation method of the modified filler is:
[0034] S01: Mix the hollow glass microspheres thoroughly in a sufficient amount of 5-7% potassium permanganate solution, then wash with water and dry;
[0035] S02: 3 to 5 parts of dried hollow glass microspheres, 1 to 3 parts of yttrium nitrate solution and 2 to 4 parts of 5% by mass sodium dodecylbenzene sulfonate solution are uniformly mixed to obtain a glass microsphere liquid;
[0036] S03: adding 2 to 5 parts of sodium alginate powder and 1 to 3 parts of nano-silicon powder to 4 to 7 parts of chitosan solution and stirring thoroughly, then washing with water and drying to obtain modified sodium alginate;
[0037] S04: Add 3-5 parts of kaolin, 2-4 parts of modified sodium alginate and 1-3 parts of carboxymethyl cellulose to 4-7 parts of glass microbead liquid and stir. After stirring, filter and dry to obtain a modified filler.
[0038] The mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the chitosan solution is 3-6%.
[0039] The stirring speed of the stirring treatment is 550-750 r / min, and the stirring is performed for 20-30 minutes.
[0040] The preparation method of silane coupling agent and lanthanum synergist is as follows:
[0041] S01: mixing a silane coupling agent, deionized water and an ethanol solvent in a weight ratio of 2:5:1 to obtain a modified silane coupling agent;
[0042] S02: Mix lanthanum oxide with a sufficient amount of sodium silicate solution and perform ball milling at a ball milling speed of 1000-1500 r / min for 1 hour to obtain lanthanum oxide solution;
[0043] S03: Add 2 to 5 parts of lanthanum oxide liquid and 1 to 3 parts of flaky talc powder to 5 to 8 parts of sodium citrate solution, then add 2 to 4 parts of modified silane coupling agent, stir and mix thoroughly, then wash with water, filter and dry to obtain silane coupling agent and lanthanum synergist.
[0044] The silane coupling agent is silane coupling agent KH560; the mass fraction of the sodium silicate solution is 2-5%; and the mass fraction of the sodium citrate solution is 3-6%.
[0045] A method for preparing an explosion-proof rubber-sheathed aluminum alloy conductor cable for coal mines comprises the following steps: mixing the raw materials in parts by weight, and then extruding them at a temperature of 165°C to obtain the cable of the present invention. The energy of the UV curing treatment is 65-75 MJ / cm 2 .
[0046] Example 1.
[0047] An explosion-proof rubber sheathed aluminum alloy conductor cable for coal mines, comprising the following raw materials in parts by weight:
[0048] 20 parts of rubber body, 25 parts of dioctyl terephthalate, 10-10 parts of ethylene-vinyl acetate copolymer, 6 parts of nano zinc oxide, 4 parts of modified filler, 3 parts of silane coupling agent and lanthanum synergist, 2 parts of vulcanizing agent, and 1 part of carbon black.
[0049] The rubber body is a compound of natural rubber and styrene-butadiene rubber in a weight ratio of 3:1;
[0050] The vulcanizing agent is diisotoluene peroxide.
[0051] The preparation method of the modified filler is:
[0052] S01: Mix the hollow glass microspheres thoroughly in a sufficient amount of 5% by mass potassium permanganate solution, then wash with water and dry;
[0053] S02: 3 parts of dry hollow glass microspheres, 1 part of yttrium nitrate solution and 2 parts of 5% by mass sodium dodecylbenzene sulfonate solution are mixed evenly to obtain a glass microsphere liquid;
[0054] S03: adding 2 parts of sodium alginate powder and 1 part of nano-silicon powder to 4 parts of chitosan solution and stirring thoroughly, then washing with water and drying to obtain modified sodium alginate;
[0055] S04: Add 3 parts of kaolin, 2 parts of modified sodium alginate and 1 part of carboxymethyl cellulose to 4 parts of glass microbead liquid and stir. After stirring, filter and dry to obtain a modified filler.
[0056] The mass fraction of the yttrium nitrate solution is 2%; the mass fraction of the chitosan solution is 3%.
[0057] The stirring speed of the stirring process is 550r / min, and the stirring is performed for 20min.
[0058] The preparation method of silane coupling agent and lanthanum synergist is as follows:
[0059] S01: mixing a silane coupling agent, deionized water and an ethanol solvent in a weight ratio of 2:5:1 to obtain a modified silane coupling agent;
[0060] S02: Mix lanthanum oxide with a sufficient amount of sodium silicate solution and perform ball milling at a ball milling speed of 10000 r / min for 1 hour to obtain lanthanum oxide solution;
[0061] S03: Add 2 parts of lanthanum oxide liquid and 1 part of flaky talcum powder to 5 parts of sodium citrate solution, then add 2 parts of modified silane coupling agent, stir and mix thoroughly, then wash with water, filter and dry to obtain silane coupling agent and lanthanum synergist.
[0062] The silane coupling agent is silane coupling agent KH560; the mass fraction of the sodium silicate solution is 2%; and the mass fraction of the sodium citrate solution is 3%.
[0063] Example 2.
[0064] An explosion-proof rubber sheathed aluminum alloy conductor cable for coal mines, comprising the following raw materials in parts by weight:
[0065] 25 parts of rubber body, 30 parts of dioctyl terephthalate, 15 parts of ethylene-vinyl acetate copolymer, 9 parts of nano zinc oxide, 7 parts of modified filler, 6 parts of silane coupling agent and lanthanum synergist, 5 parts of vulcanizing agent, and 3 parts of carbon black.
[0066] The rubber body is a compound of natural rubber and styrene-butadiene rubber in a weight ratio of 3:1;
[0067] The vulcanizing agent is diisotoluene peroxide.
[0068] The preparation method of the modified filler is:
[0069] S01: Mix the hollow glass microspheres thoroughly in a sufficient amount of 7% potassium permanganate solution, then wash with water and dry;
[0070] S02: 5 parts of dry hollow glass microspheres, 3 parts of yttrium nitrate solution and 4 parts of 5% by mass sodium dodecylbenzene sulfonate solution are mixed evenly to obtain a glass microsphere liquid;
[0071] S03: adding 5 parts of sodium alginate powder and 3 parts of nano-silicon powder to 7 parts of chitosan solution and stirring thoroughly, then washing with water and drying to obtain modified sodium alginate;
[0072] S04: Add 5 parts of kaolin, 4 parts of modified sodium alginate and 3 parts of carboxymethyl cellulose to 7 parts of glass microbead liquid and stir. After stirring, filter and dry to obtain a modified filler.
[0073] The mass fraction of the yttrium nitrate solution is 5%; the mass fraction of the chitosan solution is 6%.
[0074] The stirring speed of the stirring process is 750r / min, and the stirring is carried out for 30min.
[0075] The preparation method of silane coupling agent and lanthanum synergist is as follows:
[0076] S01: mixing a silane coupling agent, deionized water and an ethanol solvent in a weight ratio of 2:5:1 to obtain a modified silane coupling agent;
[0077] S02: Mix lanthanum oxide with a sufficient amount of sodium silicate solution and perform ball milling at a ball milling speed of 1500 r / min for 1 h to obtain lanthanum oxide solution;
[0078] S03: Add 5 parts of lanthanum oxide liquid and 3 parts of flaky talcum powder to 8 parts of sodium citrate solution, then add 4 parts of modified silane coupling agent, stir and mix thoroughly, then wash with water, filter and dry to obtain silane coupling agent and lanthanum synergist.
[0079] The silane coupling agent is silane coupling agent KH560; the mass fraction of the sodium silicate solution is %; and the mass fraction of the sodium citrate solution is 6%.
[0080] A method for preparing an explosion-proof rubber-sheathed aluminum alloy conductor cable for coal mines comprises the following steps: mixing raw materials in parts by weight, and then extruding them at a temperature of 165° C. to obtain the cable of the invention.
[0081] Example 3.
[0082] An explosion-proof rubber sheathed aluminum alloy conductor cable for coal mines, comprising the following raw materials in parts by weight:
[0083] 22.5 parts of rubber body, 27.5 parts of dioctyl terephthalate, 12.5 parts of ethylene-vinyl acetate copolymer, 7.5 parts of nano zinc oxide, 5.5 parts of modified filler, 4.5 parts of silane coupling agent and lanthanum synergist, 3.5 parts of vulcanizing agent, and 2 parts of carbon black.
[0084] The rubber body of this embodiment is a compound of natural rubber and styrene-butadiene rubber in a weight ratio of 3:1;
[0085] The nano zinc oxide is compounded by 2-hydroxy-2-methyl-1-phenyl-1-propanone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a weight ratio of 2:1;
[0086] The vulcanizing agent is diisotoluene peroxide.
[0087] The preparation method of the modified filler is:
[0088] S01: Mix the hollow glass microspheres thoroughly in a sufficient amount of 6% potassium permanganate solution, then wash with water and dry;
[0089] S02: 4 parts of dry hollow glass microspheres, 2 parts of yttrium nitrate solution and 3 parts of 5% by mass sodium dodecylbenzene sulfonate solution are mixed evenly to obtain a glass microsphere liquid;
[0090] S03: adding 3.5 parts of sodium alginate powder and 2 parts of nano-silicon powder to 5.5 parts of chitosan solution and stirring thoroughly, then washing with water and drying to obtain modified sodium alginate;
[0091] S04: Add 4 parts of kaolin, 3 parts of modified sodium alginate and 2 parts of carboxymethyl cellulose to 5.5 parts of glass microbead liquid and stir. After stirring, filter and dry to obtain a modified filler.
[0092] The mass fraction of the yttrium nitrate solution is 3.5%; the mass fraction of the chitosan solution is 4.5%.
[0093] The stirring speed of the stirring process is 600r / min, and the stirring is performed for 25min.
[0094] The preparation method of silane coupling agent and lanthanum synergist is as follows:
[0095] S01: mixing a silane coupling agent, deionized water and an ethanol solvent in a weight ratio of 2:5:1 to obtain a modified silane coupling agent;
[0096] S02: Mix lanthanum oxide with a sufficient amount of sodium silicate solution and perform ball milling at a ball milling speed of 1250 r / min for 1 h to obtain lanthanum oxide solution;
[0097] S03: Add 3.5 parts of lanthanum oxide liquid and 2 parts of flaky talc powder to 6.5 parts of sodium citrate solution, then add 3 parts of modified silane coupling agent, stir and mix thoroughly, then wash with water, filter and dry to obtain silane coupling agent and lanthanum synergist.
[0098] The silane coupling agent is silane coupling agent KH560; the mass fraction of the sodium silicate solution is 2-5%; and the mass fraction of the sodium citrate solution is 4.5%.
[0099] A method for preparing an explosion-proof rubber-sheathed aluminum alloy conductor cable for coal mines comprises the following steps: mixing raw materials in parts by weight, and then extruding them at a temperature of 165° C. to obtain the cable of the invention.
[0100] Example 4.
[0101] An explosion-proof rubber sheathed aluminum alloy conductor cable for coal mines, comprising the following raw materials in parts by weight:
[0102] 22 parts of rubber body, 26 parts of dioctyl terephthalate, 12 parts of ethylene-vinyl acetate copolymer, 7 parts of nano zinc oxide, 5 parts of modified filler, 4 parts of silane coupling agent and lanthanum synergist, 3 parts of vulcanizing agent, and 2 parts of carbon black.
[0103] The rubber body is a compound of natural rubber and styrene-butadiene rubber in a weight ratio of 3:1;
[0104] The vulcanizing agent is diisotoluene peroxide.
[0105] The preparation method of the modified filler is:
[0106] S01: Mix the hollow glass microspheres thoroughly in a sufficient amount of 6% potassium permanganate solution, then wash with water and dry;
[0107] S02: 4 parts of dry hollow glass microspheres, 2 parts of yttrium nitrate solution and 3 parts of 5% by mass sodium dodecylbenzene sulfonate solution are mixed evenly to obtain a glass microsphere liquid;
[0108] S03: adding 3 parts of sodium alginate powder and 2 parts of nano-silicon powder to 5 parts of chitosan solution and stirring thoroughly, then washing with water and drying to obtain modified sodium alginate;
[0109] S04: Add 4 parts of kaolin, 3 parts of modified sodium alginate and 2 parts of carboxymethyl cellulose to 4-7 parts of glass microbead liquid and stir. After stirring, filter and dry to obtain a modified filler.
[0110] The mass fraction of the yttrium nitrate solution is 3%; the mass fraction of the chitosan solution is 4%.
[0111] The stirring speed of the stirring process was 560 r / min, and the stirring time was 22 min.
[0112] The preparation method of silane coupling agent and lanthanum synergist is as follows:
[0113] S01: mixing a silane coupling agent, deionized water and an ethanol solvent in a weight ratio of 2:5:1 to obtain a modified silane coupling agent;
[0114] S02: Mix lanthanum oxide with a sufficient amount of sodium silicate solution and perform ball milling at a ball milling speed of 1200 r / min for 1 h to obtain lanthanum oxide solution;
[0115] S03: Add 3 parts of lanthanum oxide liquid and 2 parts of flaky talcum powder to 6 parts of sodium citrate solution, then add 3 parts of modified silane coupling agent, stir and mix thoroughly, then wash with water, filter and dry to obtain silane coupling agent and lanthanum synergist.
[0116] The silane coupling agent is silane coupling agent KH560; the mass fraction of the sodium silicate solution is 3%; and the mass fraction of the sodium citrate solution is 4%.
[0117] A method for preparing an explosion-proof rubber-sheathed aluminum alloy conductor cable for coal mines comprises the following steps: mixing the raw materials in parts by weight, and then extruding them at an extrusion temperature of 165° C. to obtain the cable of the present invention.
[0118] The difference from Example 3 is that no modified filler is added.
[0119] Comparative Example 2.
[0120] The difference from Example 3 is that modified sodium alginate is not added to the modified filler.
[0121] Comparative Example 3.
[0122] The difference from Example 3 is that modified sodium alginate is replaced by sodium alginate.
[0123] Comparative Example 4.
[0124] The difference from Example 3 is that kaolin and carboxymethyl cellulose are not added to the modified filler.
[0125] Comparative Example 5.
[0126] The difference from Example 3 is that the glass microbead liquid in the modified filler is replaced by deionized water.
[0127] Comparative Example 6.
[0128] The difference from Example 3 is that no dry hollow glass microspheres and yttrium nitrate solution are added to the glass microsphere liquid.
[0129] Comparative Example 7.
[0130] The difference from Example 3 is that no silane coupling agent or lanthanum synergist is added.
[0131] Comparative Example 8.
[0132] The difference from Example 3 is that no modified silane coupling agent is added to the silane coupling agent and lanthanum synergist.
[0133] Comparative Example 9.
[0134] The difference from Example 3 is that no lanthanum oxide solution is added to the silane coupling agent and the lanthanum synergist.
[0135] Comparative Example 10.
[0136] The difference from Example 3 is that no flaky talc is added to the silane coupling agent and the lanthanum synergist.
[0137] The impact resistance of the product was tested routinely, and the product was immersed in an acetone solvent for 24 hours, and then placed in a 2% hydrochloric acid mist for 12 hours. The above was one cycle, and the cycle was treated 10 times. The product performance of Examples 1 to 4 and Comparative Examples 1 to 10 was tested, and the test results are as follows;
[0138]
[0139]
[0140] It can be seen from Comparative Examples 1 to 10 and Examples 1 to 4 that;
[0141] The product of Example 3 has excellent impact resistance and excellent stability in chemical resistance test treatment. As can be seen from Comparative Examples 1 to 10 and Example 3, the performance of the products has a significant deterioration trend when no modified filler, silane coupling agent and lanthanum synergist are added. The performance effect of the product is most significant when the two are coordinated and work together. No modified sodium alginate is added to the modified filler, sodium alginate is used instead of the modified sodium alginate, kaolin and carboxymethyl cellulose are not added to the modified filler, and deionized water is used as the glass microbead liquid in the modified filler. The performance of the products tended to deteriorate when the dry hollow glass microspheres were not added to the glass microsphere liquid, the yttrium nitrate solution was not added to the modified silane coupling agent and the lanthanum synergist, the lanthanum oxide liquid was not added to the silane coupling agent and the lanthanum synergist, and the flaky talc was not added to the silane coupling agent and the lanthanum synergist. Only the modified filler obtained by the modified sodium alginate prepared by the method of the present invention and the silane coupling agent and the lanthanum synergist prepared by the method of the present invention and the silane coupling agent and the lanthanum synergist were the most significant. The performance of the products obtained by replacing the modified sodium alginate prepared by the method of the present invention with raw materials such as kaolin and the silane coupling agent and the lanthanum synergist were not as obvious as those obtained by the present invention.
[0142] The present invention adopts rubber body, dioctyl terephthalate, ethylene-vinyl acetate copolymer, nano zinc oxide and vulcanizing agent, and simultaneously adds modified filler, silane coupling agent and lanthanum synergist to coordinate and work together, so that the obtained product has coordinated impact resistance and remarkable solvent resistance, corrosion resistance and stability.
[0143] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0144] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. An explosion-proof rubber-sheathed aluminum alloy conductor cable for coal mines, characterized in that: The explosion-proof rubber-sheathed aluminum alloy conductor cable for coal mines comprises the following raw materials in parts by weight: 20-25 parts of rubber body, 25-30 parts of dioctyl terephthalate, 10-15 parts of ethylene-vinyl acetate copolymer, 6-9 parts of nano zinc oxide, 4-7 parts of modified filler, 3-6 parts of silane coupling agent and lanthanum synergist, 2-5 parts of vulcanizing agent, and 1-3 parts of carbon black.
2. The explosion-proof rubber-sheathed aluminum alloy conductor cable for coal mines according to claim 1, characterized in that: The cable comprises the following raw materials in parts by weight: 22.5 parts of rubber body, 27.5 parts of dioctyl terephthalate, 12.5 parts of ethylene-vinyl acetate copolymer, 7.5 parts of nano zinc oxide, 5.5 parts of modified filler, 4.5 parts of silane coupling agent and lanthanum synergist, 3.5 parts of vulcanizing agent, and 2 parts of carbon black.
3. The explosion-proof rubber-sheathed aluminum alloy conductor cable for coal mines according to claim 1, characterized in that: The rubber body is compounded of natural rubber and styrene-butadiene rubber in a weight ratio of 3:1; The vulcanizing agent is diisotoluene peroxide.
4. The explosion-proof rubber-sheathed aluminum alloy conductor cable for coal mines according to claim 1, characterized in that: The preparation method of the modified filler is: S01: Mix the hollow glass microspheres thoroughly in a sufficient amount of 5-7% potassium permanganate solution, then wash and dry; S02: 3-5 parts of dry hollow glass microspheres, 1-3 parts of yttrium nitrate solution and 2-4 parts of 5% by mass sodium dodecylbenzene sulfonate solution are uniformly mixed to obtain a glass microsphere liquid; S03: adding 2-5 parts of sodium alginate powder and 1-3 parts of nano-silicon powder to 4-7 parts of chitosan solution and stirring thoroughly, then washing with water and drying to obtain modified sodium alginate; S04: Add 3-5 parts of kaolin, 2-4 parts of modified sodium alginate and 1-3 parts of carboxymethyl cellulose to 4-7 parts of glass microbead liquid and stir. After stirring, filter and dry to obtain a modified filler.
5. The explosion-proof rubber-sheathed aluminum alloy conductor cable for coal mines according to claim 4, characterized in that: The mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the chitosan solution is 3-6%.
6. The explosion-proof rubber-sheathed aluminum alloy conductor cable for coal mines according to claim 4, characterized in that: The stirring process is performed at a stirring speed of 550-750 r / min, and the stirring time is 20-30 min.
7. The explosion-proof rubber-sheathed aluminum alloy conductor cable for coal mines according to claim 1, characterized in that: The preparation method of the silane coupling agent and the lanthanum synergist is as follows: S01: mixing a silane coupling agent, deionized water and an ethanol solvent in a weight ratio of 2:5:1 to obtain a modified silane coupling agent; S02: Mix lanthanum oxide with a sufficient amount of sodium silicate solution and perform ball milling at a ball milling speed of 1000-1500 r / min for 1 hour to obtain lanthanum oxide solution; S03: Add 2 to 5 parts of lanthanum oxide liquid and 1 to 3 parts of flaky talc powder to 5 to 8 parts of sodium citrate solution, then add 2 to 4 parts of modified silane coupling agent, stir and mix thoroughly, then wash with water, filter and dry to obtain silane coupling agent and lanthanum synergist.
8. The explosion-proof rubber-sheathed aluminum alloy conductor cable for coal mines according to claim 7, characterized in that: The silane coupling agent is silane coupling agent KH560; the mass fraction of the sodium silicate solution is 2-5%; and the mass fraction of the sodium citrate solution is 3-6%.
9. A method for preparing an explosion-proof rubber-sheathed aluminum alloy conductor cable for coal mines as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the raw materials in parts by weight, and then extruding them into shapes at an extrusion temperature of 165° C. to obtain the cable of the present invention.
Citation Information
Patent Citations
Conductor shield material of mine cabtyre cable and preparation method of conductor shield material
CN102977420A
Sheath rubber for rubber sheath flexible cables
CN103059352A
Modified natural rubber cable sheath material
CN104292524A